Teaching Journalism in English Using ICT Method - Nikodemus Yudho Sulistyo (Fakultas Keguruan dan Ilmu Pendidikan Universitas Tanjungpura)
The rapid growth of Information and Communication Technology nowadays is a big concern. There are many advantages and disadvantages as well in this growth. Journalism as the main aspect of information is also becoming the focus. Journalism is one of the subjects taught in STBA (School of Foreign Language) Pontianak. In this research, the writer is using ICT (Information and Communications Technology) method in teaching the journalism subject. By applying the ICT method, the writer uses Internet and information and communication based technology to teach the basis of journalism. The writer also asks the involvement of the students in the form of citizen journalism. The writer asks the students to write news reports or reviews and upload them in verbumore.wordpress.com. The result intended is that the students should be able to understand the journalism subject and to be involved in the journalism activity.